DELE1 is protective for mitochondrial cardiomyopathy. (February 2023) - Huynh, Helen; Zhu, Siting; Lee, Sharon; Bao, Yutong; Pang, Jing; Nguyen, Anh; Gu, Yusu; Chen, Chao; Ouyang, Kunfu; Evans, Sylvia M.; Fang, Xi
Abstract: Mitochondrial dysfunction in heart triggers an integrated stress response (ISR) through phosphorylation of eIF2α and subsequent ATF4 activation. DAP3 Binding Cell Death Enhancer 1 (DELE1) is a mitochondrial protein recently found to be critical for mediating mitochondrial stress-triggered ISR (MSR)-induced eIF2α-ATF4 pathway activation. However, the specific role of DELE1 in heart at baseline or in response to mitochondrial stress remains largely unknown. In this study, we report that DELE1 is dispensable for cardiac development and function under baseline conditions. Conversely, DELE1 is essential for mediating an adaptive response to mitochondrial dysfunction-triggered stress in the heart, playing a protective role in mitochondrial cardiomyopathy. Graphical abstract: Unlabelled Image Highlights: DELE1 is likely dispensable for cardiac function at baseline. Mitochondrial dysfunction elicits stress signaling through DELE1 in cardiomyocyte. Cardiomyocyte loss of DELE1 worsens both fetal and adult cardiomyopathy.